Translating Part of France's Legal Heritage: Aubry and Rau on the Patrimoine - Kasirer, Nicholas (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2008)
Reading the pages of the 19th century legal treatise written by Charles Aubry (1803-1882) and Frédéric-Charles Rau (1803-1877) on the patrimony has been, for generations, a rite of passage in French legal education. The theory of the patrimony has aptly been described as fundamental for French private law and the account given by Aubry and Rau, however distant it may be from the law in force, should be read by anyone who seeks to understand the French legal mind. Drawing on the English-language civilian vocabulary that is part of Quebec legal culture, the author offers a translation of this text by Aubry and Rau with some commentary on its canonical status in French legal letters. Even in its translated form, it offers a means for the English-speaking reader to encounter a tradition of abstract rationality in legal scholarship that is part of France's legal "heritage" (itself a French patrimoine but in another sense).